Eco-friendly synthesis of Cu nanoparticles from garlic extract: Catalytic reduction of methylene blue - Nazanine Ghazzali; Esmaiel Soleimani (شیمی کاربردی روز)
Eco-friendly copper nanoparticles (NPs) were prepared from the interaction of a cheap and accessible precursor, blue alum with biomolecules (polyphenols, flavonoids, proteins, terpenoids and organic sulfur compounds) in the garlic extract as the reducing of copper(II) ions, and its protector and stabilizer. As-synthesized Cu NPs were characterized by conventional methods such as XRD, UV-Vis, FT-IR, SEM, TEM, TGA and EDX. Observing the absorption maximum at the wavelength of 580 nm in the UV-Vis spectrum of the suspension solution indicated the formation of copper nanoparticles due to its surface plasma resonance. The results of the XRD diffraction pattern showed that the average size of copper crystallite was 65 nm. The morphology of the synthesized sample by scanning electron microscope (SEM) showed that copper NPs were irregular spherical. Transmission electron microscopy (TEM) estimated the average size of copper particles to be 70 nm. The as-synthesized copper NPs were used as a nano-catalyst in the reduction process of methylene blue (MB) by sodium borohydride (NaBH4). The results showed that by increasing the amount of copper NPs, the rate of methylene blue reduction reaction increased. By adding 0.0010 g of as-synthesized copper NPs to a solution containing 25 mL of methylene blue 20 ppm and 25 mL of sodium borohydride 200 ppm, it reduced time of the reaction from 4 hours to 2 minutes and its efficiency was 77%. The complete reaction time of 25 mL of methylene blue solution with concentrations of 30, 40 and 50 ppm by 25 mL of sodium borohydride 200 ppm in the presence of 0.0010 g of copper NPs took 15, 25 and 28 minutes, respectively. The effect of solution pH showed that in a certain amount of nanoparticles, the reduction rate of methylene blue was higher in an alkaline environment.